PENERAPAN MODEL PAKEM (Partisipatif, Aktif, Kreatif, Efektif Dan Menyenangkan) TERHADAP HASIL BELAJAR MATEMATIKA - Riadhus Sholihin Zulkarnain; Hartatiana Hartatiana; Arvin Efriani (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2022)
One of the efforts to develop or implement a learning model in the classroom is the PAKEM learning model, namely learning designed to activate students, develop creativity so that learning becomes effective but still fun. This study uses a quantitative approach with experimental research type by comparing the learning outcomes of students who learn to use the Participatory, Active, Creative, Effective and Fun Model (PAKEM) and do not use the PAKEM Model. The population in this study were students of class X SMAN 20 Palembang, totaling 276 students. The sampling technique was purposive sampling with each class totaling 30 and 28 students. The type of data in this study is data on student learning outcomes obtained from the final test scores of 20 questions conducted after the study. Then the data was processed using the t-test (t-test). The results showed that students in the experimental class using the PAKEM model had an average score (80,83) higher than the control class students who did not use the PAKEM model, with an average score (66,25). Based on the calculation of the t- test obtained tcount 1.32 while at the level of confidence ttable is 1.67. Thus there is no significant effect on the application of the PAKEM learning model to the mathematics learning outcomes of class X SMA Negeri 20 Palembang.